1999
DOI: 10.1109/68.759402
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fiber Bragg grating dispersion-compensators made with holographic and e-beam written phase masks

Abstract: Experimental results of time delay ripples in dispersion compensating fiber Bragg gratings fabricated with either holographic or electron-beam written 10-cm-long phase masks are presented. Deviations from linear phase delay are dependent upon UV exposure uniformity and phase mask errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In practice, it has been confirmed that the amplitude of the GDR is smaller than that of the EB mask [8]. However, it is also known that infinitesimal faults exist in an actual H mask [8], so that the phase error still exists.…”
Section: Various Factors For Group Delay Ripple Generationsmentioning
confidence: 89%
See 4 more Smart Citations
“…In practice, it has been confirmed that the amplitude of the GDR is smaller than that of the EB mask [8]. However, it is also known that infinitesimal faults exist in an actual H mask [8], so that the phase error still exists.…”
Section: Various Factors For Group Delay Ripple Generationsmentioning
confidence: 89%
“…Among the above, a study has already been conducted with regard to item (g) [8]. It has been shown that the pitch fluctuation of the mask is a cause of short-term GDR.…”
Section: Various Factors For Group Delay Ripple Generationsmentioning
confidence: 98%
See 3 more Smart Citations